Pattern Analysis and Marketing Efficiency of Bokar in Rural Area, Batanghari Regency, Indonesia - Damayanti, Yusma; Nainggolan, Saidin; Utami, Putri (International Journal of Environment, Agriculture and Biotechnology, 2023)
Marketing is said to be efficient if it is considered capable of distributing products from farmers to the crumb rubber industry at a reasonable cost and a fair distribution of the price paid by the crumb rubber industry. For this reason, this study aims to analyze the marketing efficiency of bokar. This research was conducted in the Rural Area of Batanghari Regency, with a sample size of 77 farmers. Sampling uses the sSimple Random Sampling method. The data analysis used is quantitative descriptive analysis. with the One Way Anova test. Bokar marketing in Batanghari Regency consists of three marketing channels, namely: (1) Farmers - Auction Market - Provincial Collector Traders (PPProv) - Factory (Crumb Rubber). (2) Farmers - Village Collector Traders (PPD) - Provincial Collector Traders (PPProv) - Factory (Crumb Rubber). (3) Farmers - Provincial Collector Traders (PPProv) - Factories (Crumb Rubber). Based on the efficiency indicators of bokar marketing through marketing margin, farmer's share and profit ratio and marketing cost of bokar marketing channel I is more efficient than channels II and III. Based on the results of the One Way Anova test, the farmer's share received by bokar farmers in marketing channel I, marketing channel II and marketing channel III there is a significant difference. This means that the existence of a bokar auction market pool is able to significantly increase the efficiency of bokar marketing, and for this it is necessary to establish auction market poo in other villages.